Potentiation and Mechanism of Berberine as an Antibiotic Adjuvant Against Multidrug-Resistant Bacteria - Zhou H; Wang W; Cai L; Yang T (Infection and Drug Resistance, 2023)
Hongjuan Zhou, Wenli Wang, Long Cai, Tingting Yang Clinical Laboratory Experiment Center, Affiliated Hangzhou Chest Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Tingting Yang; Long Cai, Clinical Laboratory Experiment Center, Affiliated Hangzhou Chest Hospital, Zhejiang University School of Medicine, No. 208 East Huancheng Road, Hangzhou, 310003, People’s Republic of China, Email yang1989tingitng@126.com; cailong317@hotmail.comAbstract: The growing global apprehension towards multi-drug resistant (MDR) bacteria necessitates the development of innovative strategies to combat these infections. Berberine (BER), an isoquinoline quaternary alkaloid derived from various medicinal plants, has surfaced as a promising antibiotic adjuvant due to its ability to enhance the effectiveness of conventional antibiotics against drug-resistant bacterial strains. Here, we overview the augmenting properties and mechanisms of BER as an adjunctive antibiotic against MDR bacteria. BER has been observed to exhibit synergistic effects when co-administered with a range of antibiotics, including β-lactams, quinolones, aminoglycosides, tetracyclines, macrolides, lincosamides and fusidic acid. The adjunctive properties of BER led to an increase in antimicrobial effectiveness for these antibiotics against the corresponding bacteria, a decrease in minimal inhibitory concentrations, and even the reversal from resistance to susceptibility sometimes. The potential mechanisms responsible for these effects included the inhibition of antibiotic efflux, the disruption of biofilm formation, the modulation of host immune responses, and the restoration of gut microbiota homeostasis. In brief, BER demonstrated significant potential as an antibiotic adjuvant against MDR bacteria and is a promising candidate for combination therapy. Further research is necessary to fully elucidate its mechanism of action and address the challenges associated with its clinical application.Keywords: berberine, antibiotic adjuvant, multidrug-resistant bacteria, efflux pump, biofilm